Survival prognosis in individuals with a high spatial QRS-T angle - G. A. Muromtseva; E. B. Yarovaya; V. A. Kutsenko; E. A. Aidu; A. V. Kapustina; V. G. Trunov; Yu. A. Balanova; A. Yu. Efanov; S. A. Shalnova (Российский кардиологический журнал, 2022)
Aim. To evaluate medium-term survival without irreversible and fatal cardiovascular events in individuals with a high spatial QRS-T angle (sQRS-Ta) from a regional Russian sample.Material and methods. We analyzed 1394 electrocardiographic records from a random regional sample of men (30%) and women aged 25-64, which were included in the ESSE-RF1 study. Women were on average 5 years older than men, but there was no difference in mean age in the 45-64 groups. The follow-up period lasted 7 year; 26 irreversible events (cardiovascular death, non-fatal myocardial infarction or stroke) and 63 composite endpoints (CEs) (irreversible event or heart failure progression or revascularization) were identified. Irreversible events and composite endpoint in men were noted more often than in women as follows: 3,7% vs 1,1% (p=0,003) and 6,9% vs 3,6% (p=0,01), respectively. sQRS-Ta was estimated as the angle between the integral QRS and T vectors in the orthogonal leads. Survival was assessed by Kaplan-Meier curves using a log-rank test. Differences were considered significant at p≤0,05. Results. Sex groups did not differ in mean sQRS-Ta. sQRS-Ta ≥90o was considered to be increased. The divergence of survival curves by the end of follow-up period in men with increased sQRS-Ta relative to men with sQRS-Ta <900 was greater than in women as follows: 0,88 vs 0,96 for CE (p=0,0026) and 0,93 vs 0,96 for irreversible events (p=0,009); in women — 0,94 vs 0,98 for CE only (p=0,0016). Initial event and CE in men with increased sQRS-Ta occurred earlier than those with normal sQRS-Ta and then in women with increased sQRS-Ta. There were no differences in the frequency of sQRS-Ta increase among 45-64-year-old men and women, but irreversible events in men with increased sQRS-Ta occurred 5 times more often than in women. According to two-stage logistic regression, the probability of irreversible event in men is 4,35 times higher than in women (p=0,0002). After adjusting for sex, in individuals with increased sQRS-Ta, it is 2,75 times higher than in individuals with sQRS-Ta <90o (p=0,015).Conclusion. In men with increased sQRS-Ta (≥90o), survival without irreversible and fatal cardiovascular events was worse, and life expectancy was shorter than in men with normal sQRS-Ta or women with increased sQRS-Ta. The prognosis of irreversible events was significantly affected by male sex and sQRS-Ta increase.